2016
DOI: 10.3390/md14060111
|View full text |Cite
|
Sign up to set email alerts
|

Cembranoids from a Chinese Collection of the Soft Coral Lobophytum crassum

Abstract: Ten new cembrane-based diterpenes, locrassumins A–G (1–7), (–)-laevigatol B (8), (–)-isosarcophine (9), and (–)-7R,8S-dihydroxydeepoxysarcophytoxide (10), were isolated from a South China Sea collection of the soft coral Lobophytum crassum, together with eight known analogues (11–18). The structures of the new compounds were determined by extensive spectroscopic analysis and by comparison with previously reported data. Locrassumin C (3) possesses an unprecedented tetradecahydrobenzo[3,4]cyclobuta[1,2][8]annule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…615 The latter study also led to a revision of relative conguration of the previously reported cembranoid sinularectin 1084. Further examples of cembranoids or related metabolites included sinularcasbanes M-O 1085-1087 (Sinularia polydactyla), 616 where the absolute conguration of 1086 was secured by X-ray crystallography, anti-inammatory uprolides N-P 1088-1090 (Eunicea succinea), 617 cubitanoids (a scaffold previously speculated as being photochemically-derived from cembranoids) nanoculones A 1091 and B 1092 and cembranoids nanolobols A-C 1093-1095 (Sinularia nanolobata), 618 locrassumins A-G 1095-1102, (À)-laevigatol B 1103, (À)-isosarcophine 1104 and sarcophytoxide analogue 1105 (Lobophytum crassum), 619 casbane-type diterpenoid 1106 and diepoxycembranes 1107 and 1108 (Lobophytum sp. ), 620 and pambanolides A-C 1109-1112 and a seco-sinulochmodin analogue 1113 (Sinularia inelegans).…”
Section: Cnidariansmentioning
confidence: 99%
“…615 The latter study also led to a revision of relative conguration of the previously reported cembranoid sinularectin 1084. Further examples of cembranoids or related metabolites included sinularcasbanes M-O 1085-1087 (Sinularia polydactyla), 616 where the absolute conguration of 1086 was secured by X-ray crystallography, anti-inammatory uprolides N-P 1088-1090 (Eunicea succinea), 617 cubitanoids (a scaffold previously speculated as being photochemically-derived from cembranoids) nanoculones A 1091 and B 1092 and cembranoids nanolobols A-C 1093-1095 (Sinularia nanolobata), 618 locrassumins A-G 1095-1102, (À)-laevigatol B 1103, (À)-isosarcophine 1104 and sarcophytoxide analogue 1105 (Lobophytum crassum), 619 casbane-type diterpenoid 1106 and diepoxycembranes 1107 and 1108 (Lobophytum sp. ), 620 and pambanolides A-C 1109-1112 and a seco-sinulochmodin analogue 1113 (Sinularia inelegans).…”
Section: Cnidariansmentioning
confidence: 99%
“…The presence of the COSY but not NOESY correlations between H-1 and H-2 indicated a trans -fused lactone with α -oriented H-2, which was also supported by the proton vicinal coupling constant of H-1/H-2 ( J = 4.5 Hz) [88]. In this type of cembranoid, the E -form C=C double bond systems are usually found at C-3/C-4 and C-7/C-8 and sometimes at C-11/C-12 [23]. The missing NOESY correlations between H-20/H-11, H-19/H-7, and H-18/H-3 implied an E -configuration for these three C=C double bonds [84].…”
Section: Resultsmentioning
confidence: 92%
“…Further investigation of this genus revealed more than 250 compounds categorized into cembrane-type diterpenoids [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58], other types of diterpenoids [59,60,61,62,63,64,65], lipids […”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cembrane-type diterpenoids can be found in terrestrial and marine organisms, e.g. soft corals [73,74] and plants [75,76].…”
Section: Cembranolidesmentioning
confidence: 99%